The role and mechanisms of exosome microRNA in regulating metastasis within the tumor microenvironment of prostate cancer - Yongcheng Song; Qinzhang Wang; Bin Liang; Songnian Zou (Frontiers in Oncology)
Prostate cancer (PCa) metastasis remains a significant challenge in clinical treatment, resulting in limited effective treatment options and poor clinical outcomes. Recent studies have highlighted the important function of exosome microRNAs (miRNAs) in governing metastatic processes within the tumor microenvironment (TME). Our review examines the mechanisms by which exosomal miRNAs contribute to PCa metastasis, focusing on their involvement in regulating tumor invasion and migration, epithelial-mesenchymal transition, and modulating immune responses. The review also discusses the implications of these findings for therapeutic targeting of exosomal miRNAs, indicating that they may act as potential biomarkers for prognosis and therapeutic while offering novel avenues for treatment strategies aimed at inhibiting metastasis. By elucidating the intricate interplay between exosomal miRNAs and the TME, this review aims to providing new insights into PCa metastasis while offering a theoretical foundation for future clinical research.